Evaluation of Left Ventricular Diastolic Dysfunction in diabetic patients with preserved Ejection fraction and its association with myocardial performance index (Journal of Invasive and Clinical Cardiology, 2023)
Background: Diastolic dysfunction causes impairment of ventricular filling when the ventricle becomes stiff, relaxes slowly or incompletely. Diabetes mellitus increases the risk of diastolic dysfunction which can develop heart failure even in the absence of other co-morbidities. Tei index is an echocardiographic tool to evaluate global function of ventricle. Objective: To determine the prevalence of Left Ventricular diastolic dysfunction (LVDD) in patients with type 2 diabetes mellitus; and its association with LV myocardial performance index (Tei Index). Method: 100 patients with type 2 diabetes mellitus with normal left ventricular ejection fraction without overt cardiac disease were included. LVDD was determined as per using 2016 American Society of Echocardiology (ASE) guideline. LV Tei index was calculated by tissue doppler imaging method. Results: Mean age of the patients was 58.1 ± 12.6 years with 54 percent male. Mean HbA1C was 7.45± 0.99. 23 (23%) patients met the criteria of LVDD and 46 (46%) patients did not have LVDD. Whereas 31 (31%) of patients were categorized as indeterminate. Tei index was significantly higher in patients with LVDD (0.56±0.05 and 0.43±0.06 (p